Shaping the future of bananas: advancing genetic trait regulation and breeding in the post-genomics era - Miao, Hongxia; Zhang, Jianbin; Zheng, Yunke; Jia, Caihong; Hu, Yulin; Wang, Jingyi; Zhang, Jing; Sun, Peiguang; Jin, Zhiqiang; Zhou, Yongfeng; Zheng, Sijun; Wang, Wei; et al. (Oxford University Press, 2025)
Bananas (Musa spp.) are among the top-produced food crops, serving as a primary source of food for millions of people. Cultivated bananas originated primarily from the wild diploid species Musa acuminata (A genome) and Musa balbisiana (B genome) through intra- and interspecific hybridization and selections via somatic variation. Following the publication of complete A- and B-genome sequences, prospects for complementary studies on S- and T-genome traits, key gene identification for yield, ripening, quality, and stress resistance, and advances in molecular breeding have significantly expanded. In this review, latest research progress on banana A, B, S, and T genomes is briefly summarized, highlighting key advances in banana cytoplasmic inheritance, flower and fruit development, sterility, and parthenocarpy, postharvest ripening and quality regulation, and biotic and abiotic stress resistance associated with desirable economic traits. We provide updates on transgenic, gene editing, and molecular breeding. We also explore future directions for banana breeding and genetic improvement.